Effect of Antibiotics Combination on Multidrug Resistant Proteus mirabilis - Mohammed Oudah Hamad (Al-Qadisiyah Journal of Pure Science, 2018)
Atotal of three hundred and twenty one samples were collected from midstream urine taken from patients suffering from urinary tract infections. 39 isolates of Proteus mirabilis were isolated and identified depending on their morphological properties( cultural and microscopical) and biochemical tests. The study has declared that the ratio of separation this bacterium from women was (8.41%) and it is higher than the ratio of separation in both children and men which ranged (2.8%) and (0.93%) respectively . The antibiotics sensitivity of the isolates were tested against twenty-four antibiotics, the isolates showed high resistance. The impinem , meropenem, amikacin and ciprofloxacin were found more effective. The combination of antibiotics showed active synergism effect against multidrugs resistance of the isolates, especially between aminoglycoside (Amikacin and gentamycin) and quinolones (Ciprofloxacin and norfloxacin) and cephalosporins antibiotics(Cefotaxim and sefitrixon) and aminoglycoside antibiotics fromone sideand quinolones from other side.